Impact of acid secretion, gastritis, and mucus thickness on gastric transfer of antibiotics in rats. Issue 4 (1st October 2002) - Sherwood, P V; Wibawa, J I D; Atherton, J C; Jordan, N; Jenkins, D; Barrett, D A; Shaw, P N; Spiller, R C
Abstract : Background and aims: The success of Helicobacter pylori eradication regimens depends on gastric pH, inflammation, and mucus thickness. Our aim was to investigate the effects of acid secretion, inflammation, and mucolysis on gastric antibiotic transfer. Subjects and methods: A total of 134 anaesthetised rats were given metronidazole, amoxicillin, or clarithromycin intravenously and gastric contents were aspirated via an indwelling cannula. Acid secretion was controlled by either omeprazole or pentagastrin while gastritis was induced by infection with H pylori or dosing with iodoacetamide. Mucolysis was achieved by instilling pronase into the gastric lumen. Results: Metronidazole transfer increased with acid secretion and fell with omeprazole, independently of gastric pH. Clarithromycin was also transferred with acid but was then rapidly degraded. Omeprazole prevented this degradation, raising gastric luminal concentrations. Omeprazole did not alter amoxicillin transfer. Gastritis induced by H pylori did not alter gastric transfer of metronidazole and amoxicillin but that of clarithromycin was increased by 23%. However, gastritis induced by iodoacetamide reduced clarithromycin transfer without any effect on metronidazole or amoxicillin transfer. Pronase treatment increased amoxicillin transfer fourfold and metronidazole by 66% but reduced clarithromycin transfer by 35%. Conclusions: Metronidazole and clarithromycin are predominantly transferred with gastric acid rather than by an acid trapping mechanism. Pronase increases the appearance of amoxicillin and metronidazole in gastric secretions.